IoT-based Water Level Monitoring and Flood Alert System - Tanmay Jadhav; Abhishek Kale; Sanket Kakde; Sanket Garud; Prof. Nayana Thombare (International Journal of Scientific Research in Science and Technology, 2025)
Floods and water mismanagement are among the most critical challenges affecting human life, agriculture, and infrastructure. Traditional monitoring techniques are often inefficient, lacking real-time data and early warning mechanisms. To overcome these limitations, this project presents an IoT-based Water Level Monitoring and Flood Alert System. The system employs sensors such as ultrasonic or float sensors to continuously measure water levels in rivers, reservoirs, or tanks. A microcontroller (ESP8266/ESP32/Raspberry Pi) processes the data and transmits it to a cloud platform through Wi-Fi or GSM modules. The collected data is analyzed in real-time and displayed on a mobile application or web dashboard for remote monitoring. When the water level crosses predefined safe thresholds, the system triggers instant alerts to users via notifications, SMS, or email, enabling timely preventive action. This solution not only prevents overflow in domestic or industrial tanks but also acts as an early warning system for flood-prone regions. Thus, it contributes significantly to disaster management, water conservation, and public safety through a cost-effective, reliable, and scalable IoT-enabled approach.
Keywords: IoT; Water Level Monitoring; Flood Alert System; Ultrasonic Sensor/Float Sensor/Pressure Sensor; Raspberry Pi; Real-time Monitoring; Wireless Communication; Cloud Platfor; Mobile Application; Remote Monitoring; Smart Water Management; Disaster Management; Automation; Sustainability